Body Image of Pakistani Consumers - Tariq, Jalees; Ernest Cyril, de Run (Journal of Management Sciences, 2014)
This paper examines how media exposure, self esteem, and religiosity in uence body image of Pakistan consumers.The underpinning of this study is based on Social Comparison Theory with two additional variables (religiosity and self es- teem) for understanding understand consumer attitude towards body image. A self administered questionnaire was used. 193 persons responded at mall intercepts. The Conceptual framework was empirically tested through SEM. A positive relationship be- tween exposure to media and body image was found while negative in uence was found between self esteem and body image. No relationship was found between religiosity and body image. The results showed mixed outcomes as compared to past studies. The scope of this study is limited to one city only and hence the nding could not be generalized. Future researcher may use a larger sample drawn throughout Pakistan, and by examin- ing whether body image perception varies ethnically, age and gender. Media exposure is aecting the traditional norms and values of Pakistan culture and body image. The obsessions of the media and thin body image have to be controlled and this requires policy changes. Corporate sector might take initiative by not selecting ultra thin mod- els. They might also sponsors public service messages showing ill eects of being ultra thin, and showing that the ultra thin models are not real but is results of artworks and camera angles. Social Comparison Theory with two addition variable religiosity and self esteem has been successfully extended/empirically tested in the domain of Pakistan culture.